Effectiveness of Home-Based Pelvic Floor Muscle Training on Stress Urinary Incontinence and Quality of Life in Multiparous Women - Anandh Srinivasan; Payal Sanghavi (Medsci Publications, 2023)
Aim: This study aims to determine the effectiveness of home-based pelvic floor muscle training on decreasing the symptoms of stress urinary incontinence and improving the quality of life among multiparous women Methods: Women who were diagnosed with Stress Urinary Incontinence were invited to take part in this study. These subjects were randomly allocated to either an intervention group or a control group. A 6-week assessment of both groups were carried out for the pelvic floor muscle strength using the modified oxford grading system, for the severity of Incontinence, the ICIQ- short form was used, & for the Quality of Life, Incontinence QoL Scale was used. Results: A total of 60 subjects were included in the study. At the baseline, both the groups were similar in terms of PFM strength, ICIQ score& Incontinence QoL Scale. At the end of 6 weeks of assessment, there was a significant difference (p<0.001) between the control & the intervention group in terms of MOGS, ICIQ score and Incontinence QoL Scale score. Conclusion: The home-based pelvic floor muscle training was found as a safe and effective intervention in decreasing the severity of symptoms and improving the quality of life in multiparous women with SUI.